Hubungan Mutu Pelayanan dengan Tingkat Kepuasan Pasien Rawat Inap di Puskesmas Pasir Panjang Kota Kupang - Nurulsiam Siwa Salasim; Rina Waty Sirait; Masrida Sinaga (Media Kesehatan Masyarakat, 2021)
Quality of service is one of the elements that can affect patient satisfaction when accessing health services at Primary Health Care (PHC). Dissatisfaction may indicate the low quality of PHC services. This study aims to determine the relationship of service quality with the level of satisfaction in inpatients at the Pasir Panjang PHC, Kupang City. This research was an analytical survey with a cross-sectional design. The sample of this study consisted of 118 inpatients selected by simple random sampling. The data were collected by using a questionnaire on the quality of health services and patient satisfaction with 42 items. The data analysis performed was bivariate analysis using the chi-square test. The results showed that there was a relationship between the dimensions of direct evidence (tangible), reliability, responsiveness, assurance and empathy with the satisfaction level of inpatients. PHC needs to widen the family waiting room, provide services according to the schedule to prevent the delays, and ask whether the treatment conducted meets the expectation of patients.